Association between tau uptake and verbal fluency converge in language centers. (20th December 2022) - Stevenson, Alyssa; Rahmouni, Nesrine; Therriault, Joseph; Stevenson, Jenna; Tissot, Cécile; Lussier, Firoza Z; Bezgin, Gleb; Chamoun, Mira; Pascoal, Tharick A; Gauthier, Serge; Benedet, Andréa Lessa; Vitali, Paolo; et al.
Abstract: Background: Recent studies have shown that pathological tau accumulation, a hallmark of Alzheimer's disease (AD), is closely related to cognitive deficits in older populations. Semantic deficits, measured using tests of category verbal fluency, are among the features of early clinical stages of AD presentations. While the association between semantic decline and AD biomarkers have been evaluated, the use of a novel tau positron emission tomography (PET) tracer [ 18 F]MK6240, remains relatively unexplored. The present study aims to evaluate whether tau accumulation is associated with participants' performance on both category and letter fluency neuropsychological tests and whether category fluency performance is disproportionately impaired in AD in comparison to letter fluency. Method: The study was conducted in a population of 298 individuals (188 cognitively unimpaired, 110 cognitively impaired). The D‐KEFS Category Fluency test was used to assess semantic knowledge while Letter Fluency was used to measure lexical speed access. Participants also underwent the Mini‐Mental State Examination (MMSE) to assess overall global cognitive functioning. Accumulation of tau was assessed with [ 18 F]MK6240 PET and standardized uptake value ratio (SUVRs) were calculated between 90 to 110 min post‐injection, using cerebellum grey matter as the reference region. A voxel‐based regression model evaluated the relationship between the cognitive scoring and the PET marker [ 18 F]MK6240, correcting for age, sex, education, diagnosis and RFT was used to account for multiple comparisons. Result: This study found negative associations between Category and Letter Fluency scores and tau accumulation. Notably, stronger associations were found in the Category Fluency grouping. The associated regions are mainly in the left hemisphere in language related regions and the temporal lobe. Letter Fluency scores demonstrated the strongest association in the frontal regions. Comparatively, the MMSE scores were strongly associated with tau accumulation in both right and left hemispheres. Conclusion: Tau accumulation is associated with language dysfunction and is a major driver of domain‐specific cognitive impairment across the AD spectrum. Associations were more pronounced in the left hemisphere for both semantic knowledge and lexical speed. These results also suggest that tau accumulation is more strongly associated with semantic knowledge as indicated by uptake in language related areas.